Mathematical Details on a Cancer Resistance Model - Greene, James M.; Sanchez-Tapia, Cynthia; Sontag, Eduardo D. (Frontiers in Bioengineering and Biotechnology, 2020)
One of the most important factors} limiting the success of chemotherapy in cancer treatment is the phenomenon of drug resistance. We have recently introduced a framework for quantifying the effects of induced and non-induced resistance to cancer chemotherapy~\cite{Greene2019,Greene2018}. In this work, we expound on the details relating to an optimal control problem outlined in~\cite{Greene2018}. The control structure is precisely characterized as a concatenation of bang-bang and path-constrained arcs via the Pontryagin Maximum Principle and differential Lie algebraic techniques. A structural identifiability analysis is also presented, demonstrating that patient-specific parameters may be measured and thus utilized in the design of optimal therapies prior to the commencement of therapy. For completeness, a detailed analysis of existence results is also included.